Paternal uniparental disomy 11p15.5 in the pancreatic nodule of an infant with Costello syndrome: Shared mechanism for hyperinsulinemic hypoglycemia in neonates with Costello and Beckwith–Wiedemann syndrome and somatic loss of heterozygosity in Costello syndrome driving clonal expansion. Issue 3 (17th November 2015) - Gripp, Karen W.; Robbins, Katherine M.; Sheffield, Brandon S.; Lee, Anna F.; Patel, Millan S.; Yip, Stephen; Doyle, Daniel; Stabley, Deborah; Sol‐Church, Katia
Abstract : Costello syndrome (CS) entails a cancer predisposition and is caused by activating HRAS mutations, typically arising de novo in the paternal germline. Hypoglycemia is common in CS neonates. A previously reported individual with the rare HRAS p.Gln22Lys had hyperinsulinemic hypoglycemia. Autopsy showed a discrete pancreatic nodule. The morphologic and immunohistochemistry findings, including loss of p57 Kip2 protein, were identical to a focal lesion of congenital hyperinsulinism, however, no KCNJ11 or ABCC8 mutation was identified and germline derived DNA showed no alternation of the maternal or paternal 11p15 alleles. Here we report paternal uniparental disomy (pUPD) within the lesion, similar to the pUPD11p15.5 in Beckwith–Wiedemann syndrome (BWS). The similar extent of the pUPD suggests a similar mechanism driving hyperinsulinemia in both conditions. After coincidental somatic LOH and pUPD, the growth promoting effects of the paternally derived HRAS mutation, in combination with the increased function of the adjacent paternally expressed IGF2, may together result in clonal expansion. Although this somatic LOH within pancreatic tissue resulted in hyperinsulinism, similar LOH in mesenchymal cells may drive embryonal rhabdomyosarcoma (ERMS). Interestingly, biallelic IGF2 expression has been linked to rhabdomyosarcoma tumorigenesis and pUPD11 occurred in all 8 ERMS samples from CS individuals. Somatic KRAS and HRAS mutations occur with comparable frequency in isolated malignancies. Yet, the malignancy risk in CS is notably higher than in Noonan syndrome with a KRAS mutation. It is conceivable that HRAS co‐localization with IGF2 and the combined effect of pUPD 11p15.5 on both genes contributes to the oncogenic potential. © 2015 Wiley Periodicals, Inc.